Sexual Orientation, Gender Identity, and Romantic Relationships in Adolescents and Adults with Autism Spectrum Disorder - Dewinter, J. (J Autism Dev Disord, 2017)
This study compared sexual orientation and romantic relationship experience in a large sample of adolescents and adults with autism spectrum disorder (ASD) (n = 675) and general population peers (n = 8064). Gender identity was explored in the ASD group in relation to assigned gender at birth. Compared to general population peers, more people with ASD, especially women, reported sexual attraction to both same- and opposite-sex partners. About half of the participants with ASD was in a relationship (heterosexual in most cases) and most of them lived with their partner. A notable number of autistic participants, again more women than men, reported gender non-conforming feelings. Attention to gender identity and sexual diversity in education and clinical work with people with ASD is advised.